До проблеми контактів між київською та черняхівською культурами на ранньому етапі їх розвитку - Терпиловський, Р.В. (Археологія, 2002)
У статті проаналізовано певні аспекти контактів між київською та черняхівською культурами на прикладі двох широко досліджених поселень: Глеваха у Середньому Подніпров’ї та Боромля 2 на сході Дніпровського Лівобережжя. Розглянуто гіпотезу про виникнення пам’яток типу Боромля внаслідок переселення на схід частини черняхівського населення з верхів’їв Дністра та Західного Бугу. Некоторые аспекты ранних контактов между этими культурами анализируются на примере двух широко исследованных поселений: Глеваха в Среднем Поднепровье и Боромля 2 на востоке Днепровского Левобережья. Нижние горизонты этих памятников, датируемые второй половиной ІІІ — началом IV вв., относятся к киевской культуре, однако затем судьба их была различной: обитатели Глевахи сохранили самобытность, а население Боромли вошло в состав черняховской общности. Рассматривается также гипотеза о возникновении памятников типа Боромля в результате переселения на восток части черняховских племен из верховьев Днестра и Западного Буга. Отмечается, что цепочка черняховских памятников с праславянекими чертами охватывает практически всю северную часть лесостепной Украины. Более однородным праславянским массивом III—V вв. является северный сосед черняховских племен — население киевской культуры. Some aspects of the early contacts between these two cultures have been analyzed using the example of two extensively investigated settlements: Glevakha in the Middle Dnieper area and Boromlya 2 in the East of the Dnieper Left Bank territory. The lower horizons of these monuments, datable to the second half of the 3rd century— the beginning of the 4th centuries—refer to the Kyiv culture, though later their destiny was different: the settlers of Glevakha preserved their originality, and the population of Boromlya was included to the complement of the Cherniakliov community. The hypothesis about the appearance of monuments of Boromlya type as the result of the moving of a part of the Cherniakhov tribes from the Upper Dniester and the Western Bug is proposed. It is also noted that the chain of Cherniakhov monuments, with their pre-Slavic features, embraced almost all of the Northern part of the forest-steppe zone of Ukraine. The northern neighbor of the Cherniakhov tribes — the population of Kyiv culture—was a more homogeneous pre-Slavic area of the 3rd—5th centuries.